Finite Sample Theory and the Distributions of Alternative Estimators of the Marginal Propensity to Consume - Phillips, P. C. B. (Review of Economic Studies, 1980)
Journal Article Finite Sample Theory and the Distributions of Alternative Estimators of the Marginal Propensity to Consume Get access P. C. B. Phillips P. C. B. Phillips Yale University and University of Birmingham Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 47, Issue 1, 1980, Pages 183–224, https://doi.org/10.2307/2297109 Published: 01 January 1980